Prevalence of HCV among Drug Addicts in Lahore and its Peripheries - Abdul Basit Malik; Uzma Hanif; Saleem Bukhari; Mobina Ulfat; Saiqa Ishtiaq (International Journal of Phytomedicine, 2015)
HCV continues to be a major health threat globally; approximately 130 million people are infected around the world. The aim of the study was to describe the HCV prevalence in drug addicts the most deprived, isolated and most of the times poor part of our community. This was a cross sectional study focusing the drug addicts under treatment in rehabilitation centers. A total of 92 drug addicts were recruited from four different centers at Lahore including Silverlining Lahore, Silverlining Sheikhupura, Roshan Mustaqbil Lahore and Panah Lahore. All the subjects were tested for HCV RNA PCR, SGPT and SGOT. Out of 92 subjects 23 (25%) were HCV positive and remaining 69 (75%) were HCV negative concluding the drug addicts a higher risk group. Among the HCV positive IDU`s showed a greater percentage 78% (18) and non-IDU`s only 22% (05) proving the injection users the highest risk group. The HCV positive drug users also turned up with a much high SGPT and SGOT levels with a mean of 92 U/L and 72 U/L respectively as compared to that of HCV negative subjects which were 23 U/L and 27 U/L respectively. Drug addicts and specially IDU`s are the highest risk group for developing the HCV infection as concluded by the study and their massive awareness, focus on HCV treatment and also to check the other blood borne diseases are major suggestions advised by the research.